2021
DOI: 10.1177/23992026211064711
|View full text |Cite
|
Sign up to set email alerts
|

A structural equation modeling of supply chain strategies for artemisinin-based combination therapies in Uganda

Abstract: Introduction: Malaria is a killer disease in the tropical environment; artemisinin-based combination therapies (ACTs) play a central role in treating malaria. Thus, the supply and presence of ACT drugs in hospitals are a key feature in the fight against malaria. Supply chain management literature has focused on the private sector, and less attention has been paid to the public sector, especially hospitals. Aim: This study uses an interdisciplinary lens in investigating how to boost the supply and distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Furthermore, it contributes to disruptions often witnessed across several supply chain functions including forecasting, inventory management, warehouse and stores management, stock management and fails to address the commodity needs of end users (health facilities). These structural inefficiencies aggravate other supply chain challenges including insufficient coordination, inadequate financing, lack of incentivization, schemes for supply chain personnel [ 31 ], [ 44 ], [ 53 ], [ 66 ]. Regulatory frameworks and governance Governance is a critical component of a well-functioning health system [ 60 ].…”
Section: Main Textmentioning
confidence: 99%
“…Furthermore, it contributes to disruptions often witnessed across several supply chain functions including forecasting, inventory management, warehouse and stores management, stock management and fails to address the commodity needs of end users (health facilities). These structural inefficiencies aggravate other supply chain challenges including insufficient coordination, inadequate financing, lack of incentivization, schemes for supply chain personnel [ 31 ], [ 44 ], [ 53 ], [ 66 ]. Regulatory frameworks and governance Governance is a critical component of a well-functioning health system [ 60 ].…”
Section: Main Textmentioning
confidence: 99%
“…Research is reported that highlights the necessary system approach that must characterize logistics management (Shvartsburg and Zaborowski, 2019), as well as a required strategic conception. Although investigations are reported for the multiple sub-processes that make up logistics management, the most recurrent theme is the conception of the supply chain (Nagitta and Mkansi, 2019;Zimon and Madzík, 2019;. Through an analysis of 302 publications of the 614 identified as oriented to MSMEs, the orientation of these investigations was characterized according to the object of the logistics under study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nonetheless, some public health facilities in Sub-Saharan Africa run out of stock of malaria medicines, while in others, the medicines expire, leaving the majority of the impoverished populace desperate for treatment (Rassi et al, 2016;Sugiharto, 2010;Ushie et al, 2016). Achieving a malaria-free environment may be farfetched, especially in Sub-Sahara Africa, because of the multiplicity of stakeholders from the macromanagement environment (Khuluza and Heide, 2017;Mwathi and Ben, 2014), unless both the internal and external chain partners are coordinated (Nagitta and Mkansi, 2019). Hospitals ought to manage the supply and distribution interdependency of medicines with local, regional and international partners on harmonization and standards development to harness the mutual benefits and learning from the partnership.…”
Section: Introductionmentioning
confidence: 99%
“…When adopted as the first-line treatment for malaria, ACTs are either free of charge or at a highly subsidized price. In Uganda, public hospitals are vital in treating malaria-affected patients (Nagitta et al , 2021). Nonetheless, some public health facilities in Sub-Saharan Africa run out of stock of malaria medicines, while in others, the medicines expire, leaving the majority of the impoverished populace desperate for treatment (Rassi et al , 2016; Sugiharto, 2010; Ushie et al , 2016).…”
Section: Introductionmentioning
confidence: 99%